Femtosecond electron pulse compression by using the time focusing technique in ultrafast electron diffraction - 温文龙 雷晓红 胡昕 徐向晏 王俊锋 曹希斌 刘虎林 王超 党利宏 田进寿 (Chinese physics B, 2011)
We present a new model of an electron gun for generating subrelativistic femtosecond （fs） electron pulses. The basic idea is to utilize a dc acceleration stage combined with a time focusing region, the time focusing electrode generates an electron energy chirp for bunching at the target. Without considering the space charge effects, simulations of the electron gun were carried out under the conditions of different dc voltages and various slopes of the voltage added on the time focusing electrode. Tracing and simulating large numbers of photoelectrons through Monte-Carlo and finite difference methods, the electron pulses with 1 ps can be compressed to 55 fs, which will allow significant advances in the field of ultrafast diagnosis.